A four-year phytoremediation trial to decontaminate soil polluted by wood preservatives: phytoextraction of arsenic, chromium, copper, dioxins and furans. Issue 14 (5th December 2020) - Yanitch, Aymeric; Kadri, Hafssa; Frenette-Dussault, Cédric; Joly, Simon; Pitre, Frederic E.; Labrecque, Michel
Abstract: Widely used as wood preservatives for the last century, Pentachlorophenol (PCP) and chromated copper arsenate (CCA) have been shown to leach from treated surfaces and contaminate soil of wood storage sites. We performed a four-year field phytoremediation trial in southern Quebec (Canada) on a site contaminated with PCP and CCA with the following objectives: (1) assess the potential of willow, fescue, alfalfa and Indian mustard to tolerate and translocate CCA and PCP residues in their aerial tissues, (2) investigate the possibility of phytoextraction of dioxins and furans, and (3) test the effect of nitrogen fertilizer on phytoremediation performance. We showed that while nitrogen fertilization increased the chlorophyll content of plants, it did not result in a significantly greater plant biomass. We also showed that plants grown in the presence of PCP/CCA residues were able to translocate and concentrate trace elements in their aerial tissues, but also dioxins and furans (PCDD/F). This suggests that plants grown on sites polluted by PCP might contain dioxins and furans and should be treated as contaminated by these toxic chemicals. Finally, the reduction of soil contaminants at the end of the trial suggests that phytoremediation is a promising approach for decontaminating such sites.